2000
DOI: 10.1046/j.1365-2141.2000.01898.x
|View full text |Cite
|
Sign up to set email alerts
|

Four novel non‐random chromosome rearrangements in B‐cell chronic lymphocytic leukaemia: 6p24–25 and 12p12–13 translocations, 4q21 anomalies and monosomy 21

Abstract: Summary. Nine patients with previously unreported chromosome changes were identi®ed among 209 B-cell chronic lymphocytic leukaemia (CLL) cases: three patients had a translocation involving 6p24±25; three had a 12p12±13 translocation; two had 4q21 involvement (one with coexisting 6p anomaly); and two had monosomy 21.Interphase¯uorescence in situ hybridization (FISH) detected some cryptic aberrations (12, 6q±, 17pÀ, 11qÀ) in those patients with 6p translocations, whereas only a cytogenetically undetected 13q14 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Recently, 12p aberrations, as a possible primary anomaly in CLL, have been reported. Interestingly, an aggressive clinical course was observed in one of those cases with isolated 12p involvement (34). In concordance with this finding, our patient was refractory to chemotherapy and died because of disease progression, 9 months after the SLL diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, 12p aberrations, as a possible primary anomaly in CLL, have been reported. Interestingly, an aggressive clinical course was observed in one of those cases with isolated 12p involvement (34). In concordance with this finding, our patient was refractory to chemotherapy and died because of disease progression, 9 months after the SLL diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…In a molecular genetic study, allelic loss at 6q was detected in up to 15% of informative CLL patients, showing that 6q deletion may be an important event in the molecular pathogenesis of some CLL cases. 33 Interestingly, recurrent chromosome aberrations were recently described in CLL that were not associated with the classical 13qÀ, 17pÀ, 11qÀ, þ 12 anomalies, 15 suggesting that a distinct minority of CLL cases may develop through novel cytogenetic routes. …”
Section: Discussionmentioning
confidence: 99%
“…17 The 6qÀ anomaly did not appear to influence survival in previous studies. 5,15,13 An association was found between 6qÀ and a high white blood cell (WBC) count, more extensive adenopathy at presentation 15 and shorter treatment-free interval (TFI). 18 The latter finding, however, was not confirmed in another study, 16 showing no difference in terms of clinical behavior between CLL with and without 6qÀ.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We, therefore, examined whether MUM1 expression in B-CLL cell lines was due to deregulated expression as a result of t(6;14)(p25;q32), as is the case with multiple myeloma, since Cuneo et al 41) recently reported that the 6p24-25 locus was occasionally involved in non-random rearrangements in B-CLL cases. However, this hypothesis was refuted by the results of the DCFISH analysis of two B-CLL cell lines expressing MUM1.…”
Section: Discussionmentioning
confidence: 99%